Heat pumps and solar energy: A review with some insights in the future. (August 2020) - Lazzarin, R.
Abstract: A large fraction of the energy demand is due to space heating. Direct solar heating might reduce the need of fossil fuels. However the poor solar collector efficiency when outside temperature and solar radiation are low, as in the heating season, limit most of solar collectors application to domestic hot water heating. Similarly air source heat pumps are penalized just when the heating demand is higher. Then a possible solar contribution to the outside air as a heat pump cold source was first analyzed, evaluating different integration modes of the two sources. Subsequently the coupling of a ground source and a solar section appeared a more favourable application, also because solar heat could recharge the ground in periods of low or no heating demand. At the same time the solar section might reduce the length of the expensive boreholes. Solar assisted absorption heat pumps were successfully experimented. Recently studies were devoted to a solar assistance of heat pumps by PV/T collectors, that offer both a fraction of the electricity to drive the heat pump and a solar assistance to the heat pump cold source, be it the ground or the outside air.